Alright First you combine the like terms.
9n - 3n = 6n
21 - 24 = -3
Rewrite the simplified equation
6n - 3 = 0
Solve for n
6n = 3
n = 3/6
n = 1/2
Ask if you need more help! :)
Answer:
it is 20.5
Step-by-step explanation:
you need to add all of the numbers together
Answer:
(y−2)29−x225=1
Step-by-step explanation:
Answer:.40 cents
Step-by-step explanation: divide the total cost by the amount of items you have.
If you would like to evaluate 6 * [5 * (3 - 9) - 1] + 2 / 7 * (8 - 2) + 4, you can calculate this using the following steps:
6 * [5 * (3 - 9) - 1] + 2 / 7 * (8 - 2) + 4 = 6 * [5 * (-6) - 1] + 2/7 * 6 + 4 = 6 * [- 30 - 1] + 12/7 + 4 = 6 * [- 31] + 12/7 + 4 = - 186 + 12/7 + 4 = - 182 + 12/7 = - 1274/7 + 12/7 = - 1262/7
The correct result would be - 1262/7.